2021
DOI: 10.1101/2021.02.08.21251386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemic dynamics in inhomogeneous populations and the role of superspreaders

Abstract: A variant of the SIR model for an inhomogeneous population is introduced in order to account for the effect of variability in susceptibility and infectiousness across a population. An initial formulation of this dynamics leads to infinitely many differential equations. Our model, however, can be reduced to a single first-order one-dimensional differential equation. Using this approach, we provide quantitative solutions for different distributions. In particular, we use GPS data from ~107 cellph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…After completion of this work, similar ideas for capturing individual variation with mean-field epidemic models were elaborated (Britton et al 2020;Di Lauro et al 2021;Kawagoe et al 2021;Neipel et al 2020;Rose et al 2021;Tkachenko et al 2021). These recent developments were largely prompted by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After completion of this work, similar ideas for capturing individual variation with mean-field epidemic models were elaborated (Britton et al 2020;Di Lauro et al 2021;Kawagoe et al 2021;Neipel et al 2020;Rose et al 2021;Tkachenko et al 2021). These recent developments were largely prompted by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the authors show that other initial distributions converge towards gamma through the process of contagion. Other authors (Kawagoe et al 2021) derive epidemic final sizes assuming alternative distributions of susceptibility, considering in addition that infectivity may exhibit some correlation with susceptibility (such as in the variable connectivity models analyzed here). They compare numerical results for gamma and lognormal distributions with those obtained using an empirical distribution of individual contacts derived from cell phone geolocation data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemic outbreaks in the last two decades have provided the scientific community with a wealth of material to study these questions, going beyond the classic Susceptible-Infected-Recovered (SIR) theory with perfect mixing [2][3][4][5][6]. Several studies have shown how the total epidemic size can be affected by factors such as inhomogeneity in transmission rates [7][8][9][10][11][12][13][14] or in the mode of transmission [15,16]. Classically, motion of individuals was taken into account by introducing diffusion terms in the standard SIR equations, allowing the emergence of spatio-temporal patterns [17][18][19][20].…”
mentioning
confidence: 99%